Gene flow and the maintenance of species boundaries. Issue 7 (20th December 2013) - Larson, Erica L.; White, Thomas A.; Ross, Charles L.; Harrison, Richard G.
Abstract Hybrid zones are regions where individuals from genetically differentiated populations meet and mate, resulting in at least some offspring of mixed ancestry. Patterns of gene flow (introgression) in hybrid zones vary across the genome, allowing assessment of the role of individual genes or genome regions in reproductive isolation. Here, we document patterns of introgression between two recently diverged species of field crickets. We sampled at a very fine spatial scale and genotyped crickets for 110 highly differentiated single nucleotide polymorphisms (SNPs) identified through transcriptome scans. Using both genomic and geographic cline analysis, we document remarkably abrupt transitions (<100 m) in allele frequencies for 50 loci, despite high levels of gene flow at other loci. These are among the steepest clines documented for any hybridizing taxa. Furthermore, the cricket hybrid zone provides one of the clearest examples of the semi‐permeability of species boundaries. Comparisons between data from the fine‐scale transect and data (for the same set of markers) from sampling a much larger area in a different region of the cricket hybrid zone reveal consistent patterns of introgression for individual loci. The consistency in patterns of introgression between these two distant and distinct regions of the hybrid zone suggests that strong selection is acting to maintain abrupt discontinuities within the hybrid zone and that genomic regions with restricted introgression likely include genes that contribute to nonecological prezygotic barriers.